Land, cows, and bullets: An untold history of cattle ranching during the armed conflict in Colombia, 1980–2010 - Triana Ángel, Natalia; Burkart, Stefan; Pazos Cárdenas, Mateo (Frontiers Media, 2024)
This article reflects on the history of cattle ranching in Colombia and how it was impacted by the armed conflict in the country and its regions, and the transformation amongst decades of forms of violence and actors involved in this scenario. To conduct the analysis, a review of academic literature on the relationship between cattle ranching and armed conflict in Colombia and some African countries was carried out. Subsequently, a database of 206 violent events related to cattle ranching was constructed, covering three decades of armed conflict (1980–2010), based on primary sources from reports, police evidence, and testimonies of two previous databases. This database contributed to the analysis of the impact of violence on the cattle ranching industry. Thus, this article contributes to the understanding of the history of cattle ranching in Colombia and to the complex transitional process in Colombia today. It demonstrates that productivity and efficiency have not always been the prevailing principles in the history of the cattle industry, but that land tenure and accumulation have operated as a way of securing power by the agrarian and political elites of the country. Such approaches are crucial for comprehending the historical connection between conflict and cattle ranching, especially if the aim for this sector is to adapt to a logic of productivity and innovation in the contemporary world. Also, the findings show that further research on these topics, i.e., related to current environmental and social problems such as climate change, food security, and new social and geopolitical challenges, is needed.